Design, synthesis and DSSC performance of o-fluorine substituted phenylene spacer sensitizers: effect of TiO2 thickness variation. Issue 41 (5th October 2016) - Bhim Raju, Telugu; Vaghasiya, Jayraj V.; Afroz, Mohammad Adil; Soni, Saurabh S.; Iyer, Parameswar Krishnan
Abstract : The influence of o -fluorine substituted phenyl π-spacer dyes with varying donors and different TiO2 film thickness of 9 and 12 μm show improved V oc, J sc and PCE measured under one sun. Abstract : The influence of TiO2 film thickness on the performance of DSSCs with a new series of dyes having ortho -fluorine substituted phenyl spacers and different donor moieties is reported. Optical, electrochemical, molecular orbital and photovoltaic properties were studied by varying the TiO2 thickness (9 and 12 μm) using these dyes. The thickness variation of TiO2 films had a significant effect on the open circuit voltage ( V oc ), short circuit current ( J sc ) and efficiency. The J sc and V oc of dye1b with a TiO2 film thickness of 12 μm (8.91 mA cm −2 and 0.63 V) were larger than those of the 9 μm film thickness device (8.40 mA cm −2 and 0.57 V). This could be due to the variation in the thickness of the TiO2 film. However, at an optimized thickness of the TiO2 film (12 μm), 1b exhibited the highest power conversion efficiency ( η ) of 4.0% (average 3.6%). This highest efficiency value for1b from 3.3% to 4.0% without using any co-absorbents was solely based on changing the thickness of the TiO2 film. In addition1b had a planar structure, whereas dyes2b and3b had three and two dimensional structures. The optimized geometry calculation of o -fluoro phenyl π-spacer dyes was ascertained by density functional theory (DFT) using the B3LYP/631G(d, p) basis set. These results reveal that dye1b has higher efficiency due to the deeper HOMO level and it exhibited better charge transfer from donor to acceptor, compared to the other dyes.